Case Report: Evolution of Humoral and Cellular Immunity in Two COVID-19 Breakthrough Infections After BNT162b2 Vaccine - Gallais, Floriane; Gantner, Pierre; Planas, Delphine; Solis, Morgane; Bruel, Timothée; Pierre, Florian; Soulier, Eric; Rossolillo, Paola; Fourati, Slim; Sibilia, Jean; Schwartz, Olivier; Fafi-Kremer, Samira (Frontiers in Immunology, 2022)
Background: SARS-CoV-2 breakthrough infections after complete vaccination are increasing whereas their determinants remain uncharacterized. Methods: We analyzed two cases of post-vaccination SARS-CoV-2 infections by α and β variants, respectively. For each participant both humoral (binding and neutralizing antibodies) and cellular (activation markers and cytokine expression) immune responses were characterized longitudinally. Results: The first participant (P1) was infected by an α variant and displayed an extended and short period of viral excretion and symptom. Analysis of cellular and humoral response 72 hours post-symptom onset revealed that P1 failed at developing neutralizing antibodies and a potent CD4 memory response (lack of SARS-CoV-2 specific CD4+IL-2+ cells) and CD8 effector response (CD8+IFNγ+ cells). The second participant (P2) developed post-vaccination SARS-CoV-2 infection by a β variant, associated with a short period of viral excretion and symptoms. Despite displaying initially high levels and polyfunctional T cell responses, P2 lacked of initial β-directed neutralizing antibodies. Both participants developed and/or increased their neutralization activity and cellular responses against all variants including β and δ variants that lasts up to 3 months after breakthrough infection. Conclusions: Analysis of cellular and humoral response suggest two possible mechanisms of breakthrough infection: a poor immune response to vaccine and viral evasion to neutralizing antibodies.